The Influence of Principal's Leadership on Teacher Performance in State Elementary Schools - Perangin-angin, Almarani Br.; Juliana, Juliana; Sari HS, Dyan Wulan; Abi, Antonius Remigius; Sitepu, Anton; Silaban, Patri Janson (JURNAL PAJAR (Pendidikan dan Pengajaran), 2025)
This study aims to find out the influence of principal leadership on teacher performance in state elementary schools 047159 the 2023/2024 academic year. The population of this study is all teachers in state elementary schools 047159 15. Sampling with non-probility y is a saturated sample with a sample of 15 teachers. The data collection instrument is in the form of a questionnaire with a scale of likert which has 5 alternatives consisting of 110 items. The validation test of the instrument used is the help of the results of SPSS version 25.0 data processing, while for the reliability of the instrument uses the Alpha Cronbach formula. Data analysis uses a simple regression analysis technique. The results of the study are shown as follows: the leadership of the principal of SD Negeri 047159 Ketaren is in the high category with a level of 33% of the results of the questionnaire that has been filled out by teachers, then the performance of SD Negeri 047159 Ketaren is in the very high category with a level of 47% of the results of the questionnaire filled out by the teachers at SD Negeri 047159 Ketaren, And based on the results of the research, the leadership of the principal has a very high influence. Based on the results of the hypothesis test, it can be calculated that the calculation value is 2.150 and the table is 1.77, so it can be concluded that Ha is accepted, namely there is an influence of the leadership of the head of the school on the performance of teachers at SD Negeri 047159 for the 2023/2024 academic year.